Compact quad‐band bandpass filter using internally coupled multimode stepped impedance resonator. Issue 3 (March 2016) - Kumar, Prahlad; Kumar, Amarjit; Pathak, N. P.
ABSTRACT: This article reports the design and analysis of a quint‐band resonator using an internally coupled multimode stepped‐impedance resonator along with meandered λ/2 resonators. Resonance frequency of the fundamental even‐ and odd‐mode along with the first higher order mode of the proposed resonator has been selected to obtain resonances at first, second, fourth, and fifth pass band while other λ/2 resonator controls the occurrence of third pass band. This resonator has been used in the design of a miniaturized quad‐band bandpass filter where transmission zeros have been used to obtain quad‐band filter response for better selectivity. Full wave simulation results along with the measured characteristics of the resonator and filter are also presented. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:708–712, 2016